Strategi Pembelajaran: Konsep dan Aplikasinya - sunhaji sunhaji (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Learning strategy is a teacher effort to create environment system that enable student to learn, or choice of teacher-student activity pattern at learning process. There are several different strategies, but only at its accentuation, namely as abstract conception thought versus its operation on three activity i.e. pre-instructional, instructional, and evaluation. As criteria to choose learning strategy there are: learning goal, skill at lesson, media being used, evaluation system, and student as subject and teacher as implementer.Â